Gonad development of hard clam (Meretri xlyrata) - Hamli, Hadi; Idris, Mohd Hanafi; Mustafa Kamal, Abu Hena; Rajaee, Amy Halimah (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Hard clam are mollusc belongs to bivalvia class that dominating the benthic area from deep sea to lowland area particularly tropical area. This invertebrate is suspension feeder that feeds upon plankton, detritus and dissolved organic matter as the source of metabolic energy to keep it grow. Those foods source are abundance at the open sea which make hard clam proper for mariculture practice. Hard clam production through mariculture gradually increase each year even still behind oyster and cockle production. Knowledge regarding gonad stage development is important for hard clam culture in order to determine proper condition for spawning. Development of bivalve gonad is categorized into resting, early development, late development, mature, spawning and spawned. Gonad development and gender of Meretrix lyrata can be identified accurately through histological study.